Effects of fucoidan on growth performance, immunity, antioxidant ability, digestive enzyme activity, and hepatic morphology in juvenile common carp (Cyprinus carpio) - Fang Li; Hanchang Sun; Yang Li; Die He; Chaoying Ren; Chengke Zhu; Guangjun Lv (Frontiers in Marine Science, 2023)
Fucoidan with its excellent biological activities such as growth promotion, antioxidant and strong immunity, is widely used in animal production. The present study was conducted to investigate the influences of feeding fucoidan on growth performance, biochemical indices, immunity, the antibacterial ability of plasma, the digestive enzyme activity of the intestine, antioxidant capacity, and the histological structure of liver in juvenile common carp. Five experimental diets added with 0 (Diet 1), 500 (Diet 2), 1,000 (Diet 3), 1,500 (Diet 4), and 2,000 (Diet 5) mg/kg fucoidan were fed to triplicate groups of 30 fish (35.83 ± 0.24 g) respectively for 8 weeks. The results showed that fish fed diets with a fucoidan supplementation of 1,666.67–1,757 mg/kg might have the best growth performance (p< 0.05). The levels of plasma total protein (TP) and albumin (ALB) in Diet 3, Diet 4, and Diet 5 were higher than those in Diet 1 and Diet 2 (p< 0.05). Moreover, the contents of plasma C3, LYZ, and IgM; the antibacterial ability of serum; and the activity of SOD, CAT, POD, and GPX in the liver, and ACP, AKP, LPS, AMS, and TRY in the intestine significantly improved; the contents of LPO and MDA in the liver were notably decreased in diets with fucoidan supplement (p< 0.05). Furthermore, the activity of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) and the contents of total bilirubin (TB) and glucose (Glu) in Diet 5 were the highest among the groups. Meanwhile, proinflammatory factors (plasma IL-6 and IL-1β) had a higher expression, but anti-inflammatory factors (plasma IL-1) had a lower expression in Diet 5 (p > 0.05). It indicated that a higher dose (2,000 mg/kg) of fucoidan may induce inflammation and metabolic disorders. Interestingly, histological results of liver also indicated that dietary fucoidan intake in certain amounts (500–1,500 mg/kg) could ameliorate hepatic morphology, but the high dosage (2,000 mg/kg) probably damaged the liver. To the best of our knowledge, this is the first study on the application of fucoidan as a functional additive to juvenile common carp. The results of the present study can be used to guide the application of fucoidan in healthy aquaculture and can further reveal the effect and mechanism of fucoidan on the nutritional physiology of aquatic animals.